DIPLOMASI PERTAHANAN INDONESIA TERHADAP MALAYSIA UNTUK MEMPERKUAT KEAMANAN DI ASIA TENGGARA (STUDI MENGENAI LATIHAN MILITER BERSAMA) - Muldani, Rizki; Dermawan, Windy; Suharmono, Munip (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
In the dynamic geopolitical landscape of Southeast Asia, maintaining strong defense relations between neighboring countries is crucial for regional stability and security. This study explores Indonesia's defense diplomacy practices toward Malaysia through joint military exercises. In addition, this study discusses how these exercises contribute to the broader objectives of regional security, including counterterrorism, maritime security, and disaster response. This study uses a qualitative research method with data collection through interviews with several relevant informants, documentation studies, and literature studies. The theories and concepts used in this study are Defense Diplomacy and Regional Security. This study finds that defense diplomacy and joint military exercises are instruments to strengthen Indonesia-Malaysia relations and advance collective security in Southeast Asia. Building trust, enhancing capabilities, and encouraging dialogue contribute to a more resilient and cohesive regional security architecture, promoting peace and stability in the Asia Pacific region.